Revisiting the Role of Physiology and Biochemistry in Salt Tolerant Genotype Development - Maiti, Ratikanta; Satya, Pratik (International Journal of Bio-resource and Stress Management, 2023)
Salinization is one of the major abiotic stress problems of present day agriculture and perhaps is going to be the biggest problem in the future agrarian system. Most of the land plants, except halophytes cannot withstand saline conditions beyond 100 mμ salt concentration. The crop plants are more susceptible and exhibits productivity loss beyond 50 mμ salt concentration and succumb completely in the range of 100-300 mμ salt concentration. Presently, about 6% of world’s land is affected by either salinity or sodicity, which when judged as proportion of irrigated cultivated land, (most productive soil) about 20% area is affected by salinity. It has been estimated that every three minute, we are losing 1 ha of arable land due to salinity.....